Cardiovascular events and death after myocardial infarction or ischemic stroke in an older Medicare population. Issue 3 (25th February 2019) - Li, Suying; Peng, Yi; Wang, Xinyue; Qian, Yi; Xiang, Pin; Wade, Sally W.; Guo, Haifeng; Lopez, J. Antonio G.; Herzog, Charles A.; Handelsman, Yehuda
Abstract : Background: Survivors of myocardial infarction (MI) or ischemic stroke (IS) are at high risk for subsequent cardiovascular events. Hypothesis: Older patients with prior MI or IS are at risk for recurrent cardiovascular events, and comorbidities such as diabetes may increase this risk. Methods: Two cohorts were studied in a retrospective Medicare 20% random sample—a 2008 cohort with up to 6 years of follow‐up (MI, N = 26 460; IS, N = 17 566) and a 2012 cohort with 1 year of follow‐up (MI, N = 26 548; IS, N = 17 728). Results: In older patients who survived an event of MI or IS (2012 cohort), 7.2% had a recurrent MI and 6.7% had a recurrent IS in the first year; 32% died. Accounting for multiple recurrent events (2012 cohort), the event rates per 100 patient‐years were 11.6 and 10.2 for the MI and IS cohorts, respectively. Cumulative incidence of recurrence (2008 cohort) increased from 7.7% at 1 year to 14.3% at 6 years for recurrent MI and from 6.7% at 1 year to 13.4% at 6 years for recurrent IS. Comorbid diabetes (2012 cohort) was significantly associated (adjusted risk ratio) with MI recurrence (1.44) and risk of coronary revascularization (1.23) in the MI cohort and with IS recurrence (1.26) in the IS cohort. Conclusion: In this older population with prior MI or IS, high rates of recurrent cardiovascular events and multiple recurrent events were observed. These findings highlight the need for aggressive intervention for secondary prevention and management of comorbidities in high‐risk patients, particularly those with diabetes.